A 12-Year Follow-up on the Long-Term Effectiveness of the Quadrivalent Human Papillomavirus Vaccine in 4 Nordic Countries. (1st October 2017) - Kjaer, Susanne K; Nygård, Mari; Dillner, Joakim; Brooke Marshall, J; Radley, David; Li, Meng; Munk, Christian; Hansen, Bo T; Sigurdardottir, Lara G; Hortlund, Maria; Tryggvadottir, Laufey; Joshi, Amita; et al.
Abstract : We summarize the long-term effectiveness of quadrivalent human papillomavirus (qHPV) vaccine in Nordic women, followed via different national registries. qHPV vaccine effectiveness remains above 90% for at least 10 years, with a trend toward continued effectiveness up to 12 years. Abstract: Background: The long-term effectiveness of the quadrivalent human papillomavirus (qHPV) vaccine was assessed by monitoring the combined incidence of cervical intraepithelial neoplasia (CIN2, CIN3), adenocarcinoma in situ (AIS), and cervical cancer related to HPV16 or HPV18. Methods: Women from Nordic countries of Denmark, Iceland, Norway, and Sweden who received a 3-dose regimen of the qHPV vaccine in the beginning of FUTURE II (Females United to Unilaterally Reduce Endo/Ectocervical Disease; V501-015, base study NCT00092534) are followed through different national registries. Effectiveness analyses were conducted approximately 2 years following completion of the base study and occur approximately every 2 years thereafter for 10 years (ie, 14 years from day 1 of the base study). Vaccine effectiveness against HPV16/18-related CIN2 or worse (CIN2+) was estimated by comparing the observed incidence with the expected incidence of CIN2+ in an unvaccinated cohort using historical registry data. Results: In the per-protocol population (2084 women) analysis of effectiveness after the first 12 years, there were no breakthrough cases of HPV16/18 CIN2+ after 9437 person- years of follow-up. Statistical power was sufficient to conclude that qHPV vaccine effectiveness remains above 90% for at least 10 years. The number of person-years during the follow-up interval of 10–12 years is continuing to accrue and shows a trend toward continuing effectiveness of the vaccine during that period. Conclusion: The qHPV vaccine shows continued protection in women through at least 10 years, with a trend for continued protection through 12 years of follow-up. Clinical Trials Registration: NCT00092534. Study Identification: V501-015